Development of Fish Chakli from Pangasius Mince and Its Storage Study - Hina Alim; K. A. Martin Xavier; S. S. Gangan; A. K. Balange (Journal of Indian Fisheries Association, 2017)
Chakli is a famous snack product in many parts of the country, particularly Maharashtra, Goa, Gujarat and Tamilnadu. This type of product is rich in carbohydrate and by adding fish mince, the amount of animal protein can be increased as fish is good source of protein. Further, use of fish mince in such products also adds peculiar taste to the product. Therefore, an attempt has been made to standardize the recipe and method for making fish Chakli from Pangasius mince and its storage study at room temperature. The proximate composition, quality indices and sensory analysis of the fish chakli were carried out. Freshly prepared fish chakli contained 2.48% moisture, 12.91% protein, 23.59% fat, 3.44% ash and 57.59% carbohydrate at day 0. Prepared chakli was packed in polyethylene packets and its storage study was carried out for 90 days at room temperature. Moisture content was observed to be increased whereas fat content and protein decreased gradually at the end of 90 days storage. pH reduced significantly, whereas peroxide (PV) and Thiobarbituric acid reactive substances (TBARS) values increased gradually but found within acceptable limit at the end of 90 days. The product prepared was found to be acceptable up to 90 days of storage at room temperature by the trained panelists. The findings will be useful for small scale industries as well as fishermen community in preparation and marketing of this product as a small scale business for their livelihood.